2022
DOI: 10.1002/cctc.202101800
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Covalent Organic Framework Cages with Zn Ion‐Implantation Promoting Photocatalytic H2 Evolution

Abstract: Covalent organic frameworks (COFs) are emerging as a class of photocatalyst for solar energy utilization. The separation of photogenerated excitons in COFs is crucial for their photocatalytic performance. Herein, we report a strategy to tune the electronic structure of COFs by implanting Zn ions within the framework to facilitate the separation and utilization of the photoinduced charges. Zn ions are incorporated within the shell of hollow COF cages (Zn@H-TpPa) by a sacrificial template method with a formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The more relevant literature on metalated COF-based photocatalysts for the HER is summarized in Table 6 to facilitate comparison of their properties and to provide information for designing new materials. 204,250,351,352,364,376,580,581,583,585,586,591,592 3.4.2. Photocatalytic CO 2 reduction.…”
Section: Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…The more relevant literature on metalated COF-based photocatalysts for the HER is summarized in Table 6 to facilitate comparison of their properties and to provide information for designing new materials. 204,250,351,352,364,376,580,581,583,585,586,591,592 3.4.2. Photocatalytic CO 2 reduction.…”
Section: Photocatalysismentioning
confidence: 99%
“…In 2022, Yu et al reported a Zn( ii )-involved hollow COF cage of Zn@H-TpPa for HER under visible-light irradiation. 581 Thereinto, Zn( ii ) enhances the polarity of the framework that is favorable for photogenerated charge separation. Moreover, Zn( ii ) causes the upward shift of both conduction and valence bands in H-TpPa, thus increasing the reduction potential of photogenerated electrons and promoting H 2 O reduction.…”
Section: Application Of Metalated Cofsmentioning
confidence: 99%
“…37 Nanostructuring COFs, specifically those with hollow morphologies, such as spheres, 38,46,93 bowl, 22 and capsule, 37 have shown great potential in improving their photocatalytic performance. Notably, compared with those of bulk COFs, these hollow COFs have demonstrated enhanced photocatalytic activities in photocatalytic hydrogen evolution, 22,39,72,94,95 CO 2 conversion, 38,96−98 oxidation, 37 and degradation of environmental contaminants. 19,46,85,95,99 In a pioneering work, Zhang et al reported the synthesis of two hollow nanoporous covalent triazine frameworks (CTFs) with varying chemical compositions through a templateassisted method.…”
Section: Applications Of Hollow Cofsmentioning
confidence: 99%
“…Nanostructuring COFs, specifically those with hollow morphologies, such as spheres, ,, bowl, and capsule, have shown great potential in improving their photocatalytic performance. Notably, compared with those of bulk COFs, these hollow COFs have demonstrated enhanced photocatalytic activities in photocatalytic hydrogen evolution, ,,,, CO 2 conversion, , oxidation, and degradation of environmental contaminants. ,,,, …”
Section: Applications Of Hollow Cofsmentioning
confidence: 99%
See 1 more Smart Citation